Efeitos de política fiscal nos EUA em um modelo FAVAR - Silva, Filipe Correia Gomes da (2011)
This paper aims to study the fiscal policy effects on a wide range of US macroeconomic variables. The empirical work is based upon a structural VAR with latent factors (FAVAR) and for which we develop a special identification scheme. As we estimate the factors using a principal component approach, theses estimates are very similar to observed industrial production and interest rate time series, and this is crucial for identification and instruments choice in our VAR model. Using impulse response functions we can see both production and personal consumption increase after a government expenditure exogenous shock. This effect of government expenditure is also positive among different income groups and further we find out lower classes are affected at the most after a public expenditure shock. This means this kind of consumers are probably subject to some credit rationing which difficults them to smooth consumption after an aggregate shock.